ANALISIS FAKTOR BUDAYA KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PENANGANAN KARGO DI BANDARA SOEKARNO HATTA INTERNATIONAL AIRPORT - Dinar Dewi Kania; Eko Probo; Hanifah Hanifah (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2016)
Flight safety  determined by various factors  which  related to human factors, both preflight and in-flight service. Cargo Handling  is one of the contributors of airplane crash in the air. The purpose of this study  are to obtain a profile of  Health and  Safety Culture (K3) and also to  determine the factors that shape the  Health and Safety Culture  at the level of organizations, groups, individuals and the physical environment. This study can be categorized as a  quantitative research with survey approach took place at   Soekarno Hatta International Airport. Methods of analysis  which employed in this research  are  Safety Climate Measurement Model of The British Health  Safety Commission and Factor analysis . Population of this research is 110 employees of cargo warehousing with sample 53 employees using simple random sampling technique. The result of the anylisis shows that the values of Healt and Safety Culture  in the cargo  handling at Soekarno Hatta Airport  are above the score / index average 5.0  which means that in general the whole individual in this section  posses the moderate level of  Healt and Safety values . The factor analysis  which applied has reduced 19  factors  into 11 factors that influence the Health and Safety Culture.